STUDYOF RELIGIOUS ATTITUDEAND MENTAL HEALTH AMONG ELDERLY PEOPLE (International Journal of Food and Nutritional Sciences, 2022)
Mental health among the elder generations in India is an important issue. Factors like social isolation, loss of loved ones, physical health issues, and societal stigma can contribute to mental health challenges. For a majority of older Indians, adherence to religious customs and rituals is an important aspect of their identity and provides them with a sense of purpose and community.The primary goal of the study is to examine the relationship between religious attitude and mental health among the 60+ elder generations in Jhajjar. For this purpose, a sample of 100 old people was taken from Jhajjar. Religious Attitude Scale by Rajamanikam (1989) and Psychological Well-Being Scale by Devender Singh Sisodia and Pooja Choudhary (2012) were administered and analyzed by using a t-test and Pearson‘s correlation.